Comorbidities in Psoriasis, Cross-Sectional Study in Western Nepal - Binamra Basnet; Ajay Kumar; Shreyasha Khadka (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Psoriasis is an immune mediated chronic inflammatory disorder with a worldwide prevalence of 0.5 to 11%. Prevalence of psoriasis in Nepal is around 3%. Psoriasis has many associated systemic diseases and conditions such as diabetes, hypertension, metabolic syndrome, hypothyroidism, of which the commonly associated condition is Metabolic syndrome. The objective of this study is to find the degree of association between psoriasis and other diseases such as hypothyroidism metabolic syndrome etc.